Persepsi Wajib Pajak di KPP Pratama Gresik terhadap Penggunaan Nomor Induk Kependudukan (NIK) Sebagai Pengganti Nomor Pokok Wajib Pajak (NPWP) dalam Proses Pelayanan dan Administrasi Perpajakan - Vania Adella Margaretta; Rusdi Hidayat Nugroho (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to explore the perceptions of Taxpayers registered at the Tax Service Office (KPP) Pratama Gresik regarding the use of the National Identification Number (NIK) as an alternative to the Taxpayer Identification Number (NPWP) in the tax administration process. With the new policy allowing the use of NIK as a substitute for NPWP in tax transactions, understanding the response and attitudes of taxpayers towards the implementation of this policy is crucial. This research employs a qualitative approach utilizing in-depth interview techniques with a diverse range of taxpayers representing various professions and income levels. The findings from this analysis reveal variations in taxpayers' perceptions concerning the practicality, security, and convenience of using NIK in tax transactions